Evolution of the overlying strata structure and characteristics of ground pressure behavior under the influence of tectonic stress - Zhu, Zhijie; Wang, Peng; Chen, Kun; Lv, Fei; Hong, Yin (Frontiers in Earth Science, 2024)
The evolution of overlying strata structures significantly influences the manifestation of ground pressure behavior in working faces. The mechanism through which tectonic stress influences the evolution of overlying rock structures remains unclear. To address this, we established a nonlinear dynamic mathematical-mechanical model to analyse and propose a theory for the structural evolution of overlying rock structures under tectonic stress. Based on the 8,105 working face in Tongxin Mine, China, we used theoretical calculations and numerical simulations to analyse the influence of tectonic stress on the formation and evolution of the overlying rock “plate-shell” structure. Under similar coal and rock seam distribution conditions, higher tectonic stress led to larger first failure interval of the key stratum. Consequently, the scale of the “plate-shell” structure controlled by the key stratum increased, resulting in more pronounced ground pressure behavior. The EH-4 geomagnetic method and numerical simulations indicated that the damage height of the overlying strata at the working face was 170 m. In response to the intense manifestation of mineral pressure resulting from large-scale overlying strata structure above the working face, the implementation of pre-cracking blasting can significantly reduce the failure interval of the key stratum and alleviate surrounding rock stress.